"Criminal" tribes of Punjab : a social-anthropological inquiry - Birinder Pal Singh (New Delhi : Routledge, 2010)
Contributed articles.
Includes bibliographical references and index.
Keywords: India -- Denotified tribes; India -- Social conditions